Effects of pneumatic tube systems on viscoelastic coagulation tests in septic patients and healthy individuals: protocol of the randomized controlled VETaPT-trial - Martin Mirus; Erik Buehrer; Lars Heubner; Christian Schnabel; Thea Koch; Peter Markus Spieth (Frontiers in Medicine)
IntroductionRapid coagulation assessment is crucial in emergencies, especially with acute bleeding, where timely intervention prevents shock and circulatory failure. Viscoelastic tests (VET) offer real-time insights into clot formation, fibrinolysis, and overall coagulation dynamics, often surpassing conventional lab tests. To accelerate diagnostics, hospitals use pneumatic tube systems (PTS) for blood transport. However, the effect of PTS transport on VET results remains unclear, especially with newer VET technologies and in critically ill patients, who may be more vulnerable to acceleration forces.ObjectiveThe VETaPT (Viscoelastic Testing after Pneumatic Tube Transport) trial investigates whether PTS transport influences results of three next generation VET and platelet function testing in healthy volunteers and critically ill septic patients. It explores if acceleration during transport alters coagulation and platelet function parameters and whether septic patients exhibit increased susceptibility due to their altered coagulation profiles. A goal is to define an acceleration threshold above which PTS-related effects become clinically relevant. This threshold could allow assessment of transport suitability based on force data alone, supporting wider clinical application without repeated blood testing.Study designThis prospective, randomized clinical trial includes both healthy volunteers and critically ill septic patients. Paired blood samples are collected and randomly assigned to either manual or PTS transport, with each subject serving as their own control. Acceleration forces during PTS transport are continuously recorded using a three-axis accelerometer. Samples are analyzed using standard lab tests and following point-of-care devices: ClotPro®, ROTEM® sigma, Multiplate®, and TEG6s®. The primary outcome is the difference in coagulation parameters between transport methods, evaluated in the context of measured acceleration forces.Expected resultsThis is the first study to systematically compare multiple next generation VET and platelet aggregation systems in both healthy and septic patients under controlled PTS transport conditions. It is hypothesized that PTS-induced acceleration may alter test results. Identifying a critical threshold could ensure safe, rapid blood transport without compromising diagnostic quality, potentially reducing personnel needs and expediting therapy initiation.RegistrationEthics approval was obtained from the responsible committee of the Technical University Dresden (BO-EK-12012024_1). The study is registered with the German Clinical Trials Register (DRKS00036231).